2012
DOI: 10.1098/rsif.2012.0310
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoelastic behaviour of a natural material is achieved via reversible changes in protein backbone conformation

Abstract: The egg capsules of marine prosobranch gastropods, commonly know as whelks, function as a protective encapsulant for whelk embryos in wave-swept marine environments. The proteinaceous sheets comprising the wall of whelk egg capsules (WEC) exhibit long-range reversible extensibility with a hysteresis of up to 50 per cent, previously suggested to result from reversible changes in the structure of the constituent protein building blocks. Here, we further investigate the structural changes of the WEC biopolymer at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 34 publications
3
70
0
Order By: Relevance
“…3d, e). More ambiguous are sharp bands centred at 1649 and 1324 cm −1 that could indicate either C = C stretching and CH 2 twisting vibrations of lipid molecules 24 or amide I and amide III bands of α-helical proteins 25, 26 , respectively. However, considering that slime proteins were previously reported to be highly unstructured 11 and because lipid =C-H stretching (3010 cm −1 ) is typically accompanied by a complementary peak around 1650 cm −1 , we assign these peaks to lipid vibrations 24, 27 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3d, e). More ambiguous are sharp bands centred at 1649 and 1324 cm −1 that could indicate either C = C stretching and CH 2 twisting vibrations of lipid molecules 24 or amide I and amide III bands of α-helical proteins 25, 26 , respectively. However, considering that slime proteins were previously reported to be highly unstructured 11 and because lipid =C-H stretching (3010 cm −1 ) is typically accompanied by a complementary peak around 1650 cm −1 , we assign these peaks to lipid vibrations 24, 27 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies on whelk egg capsules, which also show the a-helix ? b-sheet transition that is reversible (detailed in Section 3.1.9), have found that the process is driven more by internal energy than entropy changes [116,173].…”
Section: Wool and Hairmentioning
confidence: 99%
“…The past decade has shown a significant theoretical and experimental effort in the analysis of the thermomechanical behaviour of macromolecular materials such as muscle tissues [1], spider silks [2,3], polymers and biopolymers [4], polysoaps [5,6] and silks in general [7]. A common property of these materials [2,4,[8][9][10] is that their macroscopic history-dependent, dissipative response is the result of complex evolutions of 'semicrystalline' microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…A common property of these materials [2,4,[8][9][10] is that their macroscopic history-dependent, dissipative response is the result of complex evolutions of 'semicrystalline' microstructures. These are constituted by flexible (polymeric or protein) macromolecules reinforced by strong and stiff crystals (e.g.…”
Section: Introductionmentioning
confidence: 99%